Determination of Spatial Pattern of Urban Green Spread (Case Study: District 5 of Tehran Municipality) - SAHEL TABATABAYEE; MARYAM ROBATI; ZAHRA AZIZI (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study was to determine the spatial pattern of urban green space distribution applying the Network Analysis Process Model (ANP) and VIKOR (Case Study: District 5 of Tehran). After the Islamic Revolution, due to various reasons such as overflow of population to Tehran from the central and southern regions and the flood of refugees to Tehran, it has faced with the increase in population and development, which makes it important to study the distribution of green space in different parts of the city. Two types of questionnaires were used. The first questionnaire was completed by available sampling method from the participants in the parks of the area. The results were then analyzed using the VIKOR model. The second questionnaire was distributed among the relevant experts and analyzed using the ANP method. Considering the fact that the factors such as appropriate equipment, size and suitability for children had the highest weight, it is suggested that places for green space in the studied area should be determined in order to increase the number of green spaces. It is because, location was mentioned as an important factor. This can be achieved through the construction of parks in places close to residential areas away from military and arterial locations. Areas 5 and 2 suffered from the lack of green space and residents' dissatisfaction with the green space, thus being recommended; these are the first areas to increase green space and improve it by the municipality of the region.